The Structural Difference of Isobaric N-Glycans of Two Microalgae Samples Reveals Taxonomic Distance - Mócsai, Réka; Kaehlig, Hanspeter; Blaukopf, Markus; Stadlmann, Johannes; Kosma, Paul; Altmann, Friedrich (Frontiers in Plant Science, 2021)
Microalgae of the Chlorella clade are extensively investigated as an environmentally friendly source of renewable biofuels and high-value nutrients. In addition, essentially unprocessed Chlorella serves as wholesome food additive. A recent study on eighty commercial Chlorella preparations revealed an unexpected variety of protein-linked N-glycan patterns with unprecedented structural features, such as the occurrence of arabinose. Furthermore, MS/MS analyses of the dominant N-glycan specific to one group of products suggested it, despite being isobaric to the Man2GlcNAc2XylFuc N-glycan known from pineapple stem bromelain, to present at least two hitherto unknown protein N-glycan structures. Here we report the exact structures of these two novel N-glycan structures, elucidated by nuclear magnetic resonance spectroscopy and MS/MS, as well as on their phylogenetic context. Despite their humble size these two N-glycans exhibited a very different design with structural features unrelated to those recently described for other Chlorella-clade strains. The major glycans of this study presented several novel structural features such as substitution by arabinose or xylose of the internal N-acetylglucosamine as well as methylated sugars. ITS1 and ITS2 rDNA sequence analyses revealed that, while the xylose containing structure derived from a product primarily comprising Scenedesmus strains, the arabinose-containing glycan type related to Auxenochlorella pyrenoidosa. This is another example where characteristic N-glycan structures distinguish phylogenetically different groups of microalgae.